Impact of an inline extracorporeal membrane oxygenation hemofilter system in neonatal acute kidney injury - Azar M; Alamir A; Al Qahtani AT; Khamisa AM; Alfakeeh K (Dove Medical Press, 2018)
Mohammed Azar, Abdulrahman Alamir, Abdullah Thabet Al Qahtani, Al Mokali Khamisa, Khalid Alfakeeh Division of Nephrology, Department of Paediatrics, King Saud bin Abdulaziz University for Health Sciences, Ministry of National Guard – Health Affairs, King Abdulaziz Medical City, Riyadh, Saudi Arabia Abstract: Extracorporeal membrane oxygenation (ECMO) is considered a recognized lifesaving support for patients with cardiorespiratory failure. Acute kidney injury (AKI) and fluid overload are significant morbidity factors resulting in serious complications. The inline hemofilter system (IHS) and the continuous renal replacement therapy (CRRT) machine are different methods of renal replacement therapy for patients with ECMO. IHS is the alternate, safe dialysis modality of choice because it is user-friendly, inexpensive, and efficiently removes fluid overload and renal diffusive clearance. We report on a 20-day-old male neonate with multiple congenital cardiac defects who needed venoarterial ECMO and had AKI necessitating renal replacement therapy using IHS. The patient had stable electrolyte parameters, good ultrafiltration, and efficient diffusive clearance. He was decannulated from ECMO therapy after 9 days without any related complications. Therefore, neonatal IHS is a safe and efficient alternative approach to AKI. Keywords: extracorporeal membrane oxygenation, continuous renal replacement therapy, inline hemofilter system, cardiopulmonary bypass, acute kidney injury